Teaching Speaking Skills through Role Play at Elementary Level: An Analysis - Muhammad Safdar Bhatti (JURNAL ARBITRER, 2021)
English has won the status of International language. The quality of our expression depends on our use of speaking skills. The importance and value of speaking English have been accepted worldwide. In Pakistan, Teaching English was mainly focused upon reading and writing skills. But in today's world, listening and speaking skills have become much more important than in the past. Recently, the value of role-play in the classroom situation has become mandatory to make the teaching-learning process easy, attractive, and interesting. The implementation of role-play was expected to be an effective way to improve the learners' speaking skills. So in the present study, the focus is on this matter whether the use of role play can be beneficial in bringing a positive change in the teaching-learning process of speaking skills for elementary level learners. The collective problems of the teachers and students during speaking English were the main focus of the study. 360 students and twenty teachers of Bahawalpur region participated in this study. Pre-test, post-test, and questionnaire were used as a tool to collect the data from the respondents. The findings of the study showed that there was a significant difference between pre-test and post-test results. It was suggested that speech practice with the help of role play should be encouraged at the elementary level.